Furosemide removal in constructed wetlands: Comparative efficiency of LECA and Cork granulates as support matrix. (1st December 2017) - Machado, A.I.; Dordio, A.; Fragoso, R.; Leitão, A.E.; Duarte, E.
Abstract: The removal efficiency of LECA and cork granulates as support matrix for pharmaceuticals active compounds in a constructed wetland system was investigated using the diuretic drug Furosemide. Kinetics studies were performed testing three different concentrations of Furosemide in an ultrapure water matrix, along seven days. LECA achieved higher removal values compared to cork granulates. However, cork granulates presented a higher removal in the first 24 h of contact time compared to the other adsorbent. The kinetic studies showed that LECA and cork granulates have different adsorption behaviours for Furosemide which is controlled by different adsorption mechanisms. Both materials showed good removal efficiencies and a combination of the two should be further explored in order to applied both materials as support matrix to cope with different furosemide concentrations. Highlights: Adsorption capacity of LECA and cork granulates as support matrix was studied. LECA adsorption kinetics was depended of Furosemide initial concentration. Cork granulates presented higher adsorption capacities for lower HRT. Wetland system efficiency could be enhanced combining both filling materials.